An assessment of the arabic language programme for human sciences students at IIUM - Mohammad Lotfie, Maskanah (s.n, 2012)
This study focuses on the teaching and learning of Arabic for Human Sciences (HS) undergraduates at International Islamic University Malaysia (IIUM). Even though English is the medium of instruction for the majority of IIUM academic programmes, Arabic has long been incorporated into the curricula of Communication, English, History, Political Science, Psychology and Sociology programmes. The incorporation of the language is a measure to effectively realize the University's philosophy in augmenting Islamic perspective and value into contemporary and conventional curriculum.